2006
DOI: 10.1080/10641950500543889
|View full text |Cite
|
Sign up to set email alerts
|

Third Nerve Palsy and Serous Retinal Detachment with Preeclampsia

Abstract: Visual disturbances occur more frequently during preeclampsia than during pregnancy in general, but visual disturbances due to cranial nerve palsy are rare. We present the case of a 35-year-old preeclamptic woman with left third nerve palsy and left serous retinal detachment. The patient complained of visual disturbance and double vision soon after cesarean section. Left third nerve palsy and left serous retinal detachment were diagnosed by urgent ophthalmologic evaluation. Aneurysm and organic brain lesion we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…[57][58][59][60][61][62] In an interesting case report, bilateral serous retinal detachment was reported to reveal an occult pregnancy. 63 The onset of preeclampsia-related serous retinal detachment is sudden, the main symptoms are a visual field defect and loss of visual acuity.…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…[57][58][59][60][61][62] In an interesting case report, bilateral serous retinal detachment was reported to reveal an occult pregnancy. 63 The onset of preeclampsia-related serous retinal detachment is sudden, the main symptoms are a visual field defect and loss of visual acuity.…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…These reports describe mono-neuropathies involving CN III, VI and VII. [2][3][4][5]10 Due to a greater preponderance during the third trimester, it has been proposed that pregnancy-related CN lesions may be the result of increased extracellular fluid causing perineural oedema and neural compression 5,11 Alternatively a complex vasculopathy (including hypercoagulability) induced by preeclampsia may render the affected nerve ischaemic. 5,11 We favour an ischaemic effect in this patient due to the acuity of onset, a close association with the development of pre-eclampsia and the rarity of hypoglossal ''auto-compression''.…”
Section: Discussionmentioning
confidence: 99%
“…Only 4 case reports have been published on retinal detachment associated with placental abruption. [3][4][5][6] Hoines et al reported a woman of 40 weeks of gestation with vaginal bleeding, dizziness, and blurred vision. 4) Although her systolic blood pressure was normal (110 -120 mmHg), laboratory data showed disseminated intravascular coagulopathy (DIC) with positive proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Watanabe et al reported a woman with chronic hypertension. 5) At 28 weeks of gestation, her blood pressure was elevated at 170/107 mmHg with proteinuria (4 + ). Placental abruption occurred at 31 weeks of gestation, and emergent cesarean section saved the infant.…”
Section: Discussionmentioning
confidence: 99%